Ecce homo - Grosz, George, 1893-1959. (New York : Dover Publications, 1976)
Drawings, including 16 in full color, by master satirist and accomplished draftsman George Grosz (1893-1959). First published in 1923 but suppressed, the collection offers an unsparing vision of human nakedness, lust, greed and cruelty. The 16 watercolors reveal artist’s perception with particular clarity.
"An unabridged republication of the work originally published by the Malik-Verlag, Berlin, in 1923 ... Ausgabe C. ... The text has been newly translated specially for the present edition."
English and German.
The Roger Griffin ComFas Collection
Keywords: Grosz, George, -- 1893-1959.